Pengaruh lama penyimpanan pada suhu kamar terhadap kualitas internal telur ayam kampung yang dipelihara secara intensif - Rosmerly Bakuama; Sutan Y. G .F Dillak; Franky M. S Telupere (Jurnal Peternakan Lahan Kering, 2019)
The aims of the experiment was to study the effect of  room temprature storage time on internal depth  of indigenous chicken eggs raised in  intensive care system i.e, initial eggs weight, white n yellow eggs index. eggshell thikness, egg weight loss and airshell quality. The research used 36 eggs taken from  the hens. The experiment used Randomly Block Design with four treatments and three  replicates. The four treatments were : P0: fresh egg (no storage time); P1: 2 days storage time; P3: 4 days storage time; P4: 6 days storage time. Variables measured were egg weight, yolk and albumine index, eggshell quality, egg weight loss, and egg air space. Data were analysed with ANOVA and followed by Duncan’s Multiple Range Test, when it evaluated difference between the treatments. The results of the experiment showed that treatments had the treatment effect (P<0,05) on yolk and index, egg weight loss and air space. However, had no significant effect (P>0,05) on egg weight, albumine index and eggshell quality. Therefore, it can be concluded that storage 6 days  time did effect internal quality of eggs.